2008
DOI: 10.2174/156800908784293631
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Expression Profiles of Medulloblastoma Cell Lines Resistant to Preactivated Cyclophosphamide

Abstract: The total expression profiles of two medulloblastoma cell lines resistant to the preactivated form of cyclophosphamide (4-hydroperoxycyclophosphamide, 4-HC) were examined using the Affymetrix GeneChip U133A array. Our primary objective was to look for possible genes, other than the well-studied aldehyde dehydrogenases (ALDH) that may be involved in cyclophosphamide (CP) resistance in medulloblastomas. We present here the lists of the most highly upregulated [30 for D341 MED (4-HCR); 20 for D283 MED (4-HCR)] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Several studies have associated ALDH1B1 with functions other than acetaldehyde metabolism. A recent microarray study showed that ALDH1B1 was up-regulated in medulloblastoma cell lines resistant to cyclophosphamide, suggesting a possible role of ALDH1B1 enzyme in cancer drug resistance (Bacolod et al, 2008). Another study reported that the dynamic expression of ALDH1B1 correlated with granulocytic development of hematopoietic stem cells; in this report, the author proposed a possible role of ALDH1B1 in retinoic acid metabolism mediating the effect (Luo et al, 2007).…”
Section: Initial Characterization Of Human Aldh1b1mentioning
confidence: 70%
“…Several studies have associated ALDH1B1 with functions other than acetaldehyde metabolism. A recent microarray study showed that ALDH1B1 was up-regulated in medulloblastoma cell lines resistant to cyclophosphamide, suggesting a possible role of ALDH1B1 enzyme in cancer drug resistance (Bacolod et al, 2008). Another study reported that the dynamic expression of ALDH1B1 correlated with granulocytic development of hematopoietic stem cells; in this report, the author proposed a possible role of ALDH1B1 in retinoic acid metabolism mediating the effect (Luo et al, 2007).…”
Section: Initial Characterization Of Human Aldh1b1mentioning
confidence: 70%
“…Only in D341 previously shown to be resistant to selected cytotoxic drugs 5 ÎŒM GDC-0941 were required to achieve this level of suppression [36, 37]. We based our choice of in vitro drug concentrations on the original publication characterizing GDC-0941 as a potent and selective inhibitor of class I PI3K kinase.…”
Section: Discussionmentioning
confidence: 99%
“…First, it can always be viewed that the expression profiles of cell lines which have undergone many passages do not exactly represent the genetic events that occur in actual tumors (48). Second, the present study was restricted to the use of only seven glioma cell lines.…”
Section: Discussionmentioning
confidence: 99%